Effect of different levels of saturated solution of calcium chloride in the preparation of calcium salt of fatty acid and its effect on rumen protozoa, pH and ammonia nitrogen - Meraj, MMR; Khan, MAS; Rakhi, TA; Sarker, NR (Bangladesh Journal of Animal Science, 2013)
<!--[if gte mso 9]> <![endif]--><span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Calcium salt of fatty acid was prepared by adding 3 different levels of saturated solution of calcium chloride (CaCl2) to soybean oil. It was found that fat content was not significantly affected by calcium chloride. However, calcium chloride had significant effect on other parameters like dry matter, fat, ash and sodium. The highest calcium and fat was obtained when 3.5 parts CaCl2 were added (p<0.01). It was also observed that sun drying and drying at room temperature had no significant effect on any parameter except dry matter content. Calcium salt of fatty acid had significant anti-protozoal effect (p<0.01) in sheep. Treated group showed reduced protozoal number without affecting the rumen pH and rumen ammonia nitrogen. It was also found that the number of rumen protozoa in rumen liquor was less at 12:00 p.m. than that at 3:30 p.m. when sheep were fed 3% calcium salt. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">DOI: http://dx.doi.org/10.3329/bjas.v42i2.18489 Bang. J. Anim. Sci. 2013. 42 (2): 109-113 <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->